European champions and competition enforcement: Is DG COMP in ideological denial? - Damien Neven (Graduate Institute of International and Development Studies, 2014)
[Introduction ...] We organise the discussion (in section 1) by characterising the current position of the Commission on public policy towards industry and the interplay between competition enforcement and these policies. We then describe the main challenges to this position by the Commission's critics and identify five issues for discussion, namely (i) the scope of the public policy concern raised by the nationality of the acquirers in international transactions, (ii) the scope for support to strategic sector, (ii) the need to respond to foreign support in strategic sectors, (iii) the implementation of merger control rules which allow for the emergence of champions and (iv) the implementation of merger control rules which give companies from small member states the same opportunities as those from large member states. Each of those issues in discussed in turn (section 2 to 5). Overall, we conclude that in most instances when there is evidence in support of the arguments put forward by the critics of the Commission, these arguments can be addressed in the context of the current rules. What is required is thus possibly more of a change in enforcement than a change in the rules themselves. In particular, we find, first, that there may be a legitimate concern about the nationality of acquirers with respect to the location of research and development facilities but that this concern can probably be addressed by adopting a wider interpretation of Art 21(4) of the merger regulation. We observe, second, that there may be more scope for the identification of strategic sectors but that the grounds on which intervention can be justified towards these sectors are likely to be recognised by state aid rules. Third, we find that the substantive criteria for the assessment of mergers denies a number of transactions that would raise efficiency and profits over and above the consumer harm that they entail but that the current enforcement is likely to reinforce the bias against efficiency enhancing transactions. Short of changing the substantive criteria, much could be done by ensuring that a balanced hearing is given to efficiencies. Finally, we conclude that while it may be appropriate to give companies from small member states the same opportunities as those from larger member states, this would require a decision rule in which, unlike the current one, consumer harm in one country is balanced against consumer benefits in other country. This involves a more significant change in policy.
Keywords: 330